2017
DOI: 10.1109/tuffc.2016.2619685
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Generating Submicrometer Phase-Shift Perfluorocarbon Droplets for Applications in Medical Ultrasonography

Abstract: Continued advances in the field of ultrasound and ultrasound contrast agents have created new approaches to imaging and medical intervention. Phase-shift perfluorocarbon droplets, which can be vaporized by ultrasound energy to transition from the liquid to the vapor state, are one of the most highly researched alternatives to clinical ultrasound contrast agents (i.e., microbubbles). In this paper, part of a special issue on methods in biomedical ultrasonics, we survey current techniques to prepare ultrasound-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 79 publications
(145 reference statements)
1
88
0
Order By: Relevance
“…38 The most commonly used and favored method of producing low boiling point (<0 °C) nanodroplets of liquid decafluorobutane (DFB) (BP = −1.7 °C) or octafluoropropane (OFP) (BP =−36.7 °C) begins by producing MBs using sonication or high-speed mechanical agitation of the dispersion medium with the PFC vapor present in the headspace. 36,37,3941 While this approach results in successful production of PCCAs, the resulting NDs have a wide size distribution requiring filtering of the final sample, 42 relatively low particle counts, and most importantly, a large number of ~100 nm-sized likely non PFC-filled liposomes that are generated during MB production and condensation. In addition, spontaneous vaporization into MBs has been reported due to thermal instability of such NDs.…”
Section: Introductionmentioning
confidence: 99%
“…38 The most commonly used and favored method of producing low boiling point (<0 °C) nanodroplets of liquid decafluorobutane (DFB) (BP = −1.7 °C) or octafluoropropane (OFP) (BP =−36.7 °C) begins by producing MBs using sonication or high-speed mechanical agitation of the dispersion medium with the PFC vapor present in the headspace. 36,37,3941 While this approach results in successful production of PCCAs, the resulting NDs have a wide size distribution requiring filtering of the final sample, 42 relatively low particle counts, and most importantly, a large number of ~100 nm-sized likely non PFC-filled liposomes that are generated during MB production and condensation. In addition, spontaneous vaporization into MBs has been reported due to thermal instability of such NDs.…”
Section: Introductionmentioning
confidence: 99%
“…Since the particles are prepared by sonication, the energy input is very high, which will have a substantial impact on the final product. 14 This was the main reason that parts of PFP were lost during this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…17 A number of studies have demonstrated that US can induce liquid-gas phase transformation to generate perfluorocarbon bubbles for enhancing US imaging. 14,18,19 The mechanisms of acoustic droplet vaporation mainly include US-inherent biological effects, such as cavitation and mechanical effects and thermal effects, which trigger the phase transition of lipid perfluorocarbon encapsulated in the nanoparticle core, thus producing gas bubbles. [20][21][22][23] Commonly used PFH is converted into gas under HIFU, while the liquid-gas phase shift in PFP can be induced by LIFU due to its much lower b.p.…”
Section: Discussionmentioning
confidence: 99%
“…These agents are comprised of liquid phase perfluorocarbon droplets coated with surfactant or lipid shells, and are superheated above their boiling points at physiologic temperatures to a metastable state . Their liquid core enables prolonged circulatory persistence over commercial microbubble agents, but results in poor imaging contrast potential unless targeted to accumulate in layers, demonstrated by Lanza and coworkers . Alternatively, when droplets absorb stimulating energy—in the form of heat by ultrasound or in some cases light with multimodal droplets as demonstrated by Paproski et al, or when stimulated by appropriate pressures—droplets can change phase, expanding to form echogenic bubbles on the order of 5–6 times larger than their precursor droplet size .…”
Section: The Next Generation: Submicron Ultrasound Contrast Agentsmentioning
confidence: 99%
“…Of course, characterization of submicron agents is complicated, with the primary distribution existing near or below brightfield resolution limits of microscopy; and standard nanoscale sizing approaches estimate the particle distribution indirectly . A new generation of sizing instruments may circumvent this issue with direct measurements, but submicron sizing should be coupled with microscale sizing to eliminate outliers beyond the sensitivity of the submicron sizing instrument …”
Section: Perspectivesmentioning
confidence: 99%